Differentiating Athlete's Heart from Inherited Cardiac Pathology: The Challenge of Repolarisation Abnormalities Presenting during Anaesthesia. Issue 2 (March 2013) - Dzendrowskyj, P.; Hamilton, B.; Wilson, M. G.
This case report describes an asymptomatic healthy male professional athlete who underwent general anaesthesia for a routine orthopaedic operation. Peri-procedure, pronounced ST elevation suggestive of myocardial ischaemia manifested on the electrocardiogram lasting for four hours post-procedure, upon which the athlete developed deep and diffuse inferolateral T-wave inversion. These changes resolved spontaneously and the patient remained clinically stable throughout. This case demonstrates the clinical conundrum facing anaesthetists attempting to differentiate between repolarisation anomalies that are commonly observed in high-level athletes and those of inherited cardiac pathology, namely hypertrophic cardiomyopathy, which is the leading cause of sudden cardiac death in young athletes.